TYPE 2 DIABETES AND CANCER SCREENING: FINDINGS FROM THE MALAYSIAN COHORT STUDY - Abdullah, Noraidatulakma; Nawi, Azmawati Mohammed; Kamaruddin, Mohd Arman; Jalal, Nazihah Abd; Jamal, Rahman (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION A link between type 2 diabetes and the predisposition to colon, breast, and pancreatic cancer has been established during the last decade. However, cancer screening uptake among patients with diabetes is understudied. The study aims to identify the cancer screening uptake rate among the Malaysian Cohort (TMC) participants with diabetes. METHODOLOGY A cross-sectional study was conducted from July 2017 to March 2020. There were 905 female participants with diabetes from the Malaysian Cohort, age 35 to 65 years. RESULTS Out of the 905 participants, cancer screening tests performed were Pap smear (63.5%), mammography (46.7%), clinical breast examination (CBE) (54.7%), breast-self-examination (BSE) (49.6%) and immunochemical fecal occult blood test (iFOBT) (26.3%). These uptakes were higher compared to the general population for the performance of Pap smear (22%), mammography (3.6 to 30.9%), CBE (53.3%) and BSE (47.2%). Only the iFOBT uptake rate for the general population (79.6%) was higher than in patients with diabetes. Among those who took the iFOBT test, 14.7% had a positive result, higher than in the general population (13.1%). Although a lower colonoscopy compliance rate (31.4%) was seen in patients with diabetes compared to the general population (52.7%), colorectal cancer detection rate was higher (9.1%) compared to the general population (0.27%). CONCLUSION These results emphasize the importance of cancer screening tests in patients with diabetes as recommended by the American Diabetes Association